2015
DOI: 10.1007/s15010-015-0741-6
|View full text |Cite
|
Sign up to set email alerts
|

Tenosynovitis: a rare presentation of tuberculosis better known by hand surgeons than infectious diseases specialists

Abstract: The diagnosis of tuberculous tenosynovitis should be considered in chronic tenosynovitis. Functional prognosis may be committed without adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Some studies have found a 75% success rate with anti-tuberculosis drugs without surgery. Debridement should be performed when surgical treatment is required or antituberculosis drugs fail [7]. In our cases, recovery was achieved with antituberculosis treatment without the need for surgical intervention.…”
Section: Discussionmentioning
confidence: 71%
“…Some studies have found a 75% success rate with anti-tuberculosis drugs without surgery. Debridement should be performed when surgical treatment is required or antituberculosis drugs fail [7]. In our cases, recovery was achieved with antituberculosis treatment without the need for surgical intervention.…”
Section: Discussionmentioning
confidence: 71%
“…Rheumatoid arthritis, 1,3) tuberculosis infection, 4,5) and non-tuberculous mycobacteriosis [6][7][8] were previously reported as causes of tenosynovitis with rice bodies. There are also some reports of cases with causes that were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients have an injury history and often require multiple operations as in this case [ 1 4 ]. The presence of ‘rice bodies’ is a characteristic intraoperative finding as well as tuberculosis [ 3 , 5 ]. Although the appropriate duration of chemotherapy is unclear, past studies recommended a 1–2-year treatment period [ 4 ].…”
Section: Legendmentioning
confidence: 99%